Homemakers’ Participation in Household Decision Making (Quest Journal of Management and Social Sciences, 2023)
Purpose: This study is conducted to identify homemakers’ participation in household decision making who are the member of community-based organization.Methods: The study was conducted in ward no. 30 of Pokhara Metropolitan City, where the ward represents the smallest unit of local government. The study interviewed homemaker women who were participating in Community-based Organization. The primary data were collected from purposively sampled 120 homemaker women using structured closed ended questionnaires schedule. The collected data are processed and analysed in SPSS software where the test of association (The Chi square test) was performed to find the relationship among the variables of household decision making, together with social-economic and demographic variables.Findings: The findings show that homemakers included in study have actively participating in household decision making. The Chi square test result indicates that there is no association between age and number of children with level of homemakers’ participation in household decision making. Also, other demographic variables such as marital status, caste or ethnicity, education, and family type have no significance association with household decision making.Conclusion: From this study we can say that the participation level of the women in household decision making who are the member of community-based organization is high. The participation of women in community-based organization like women’s group, saving and cooperatives, community committees empower the women and support to build confident in household decision making.Keywords: Homemaker, Participation, Decision Making, Women, Community Based Organisation.Paper type: Research Paper